PTH-084 Bullous cutaneous vasculitis-a rare side effect to adalimumab therapy. (22nd June 2015) - Shivaji, UN; Awasthi, A; Kasturi, R; Desai, K
Abstract : Introduction: Anti-TNF(tumour necrosis factor) therapy is an effective treatment for Crohn's disease. As the usage of anti-TNF drugs increase worldwide, the proportion of reported serious side effects are expected to rise. We present a serious adverse reaction to Adalimumab. Method: Case A 20 year old gentleman with background of Crohn's disease with previous terminal ileal resection and Juvenile Idiopathic arthritis (JIA) had been on Adalimumab (Humira, Abbvie, USA), for dual indication, on a dose of 40mg per week since 2010 and was in remission. He presented to hospital in September 2014 with an erythematous maculo-papular rash distributed over his lower limbs, trunk and upper limbs. Initial blood tests showed raised inflammatory markers with no other abnormality and a vasculitis screen was negative. He had dramatic worsening of the rash while in hospital with rapid development of new lesions and bullous transformation of some of the existing lesions with necrotic areas. A skin biopsy showed severe cutaneous leucocytoclastic vasculitis. Results: He was treated with high-dose intravenous Methyl-Prednisolone and was later switched to oral therapy. He improved over the next 8 weeks with reducing dose of Prednisolone. Anti-TNF drug therapy was the likely cause of the cutaneous vasculitis in absence of another specific trigger and based on existing literature, cutaneous vasculitis secondary to anti-TNF therapy is one of the side effects which may require drug withdrawal, and can be potentially serious and debilitating. There have been very few case reports worldwide of cutaneous vasculitis secondary to anti-TNF therapy, with fewer cases reported secondary to Adalimumab. According to current literature, the average duration of treatment before patients developed a major cutaneous reaction was noted to be 36 months, with all responding to drug withdrawal. Conclusion: We believe this is the first reported case of bullous vasculitis of this degree of severity, secondary to Adalimumab, involving nearly 63% of body surface area (Rule of 9s) with full thickness involvement. (Picture) As the use of anti-TNF drugs increases worldwide, it is worth considering them as a possible cause of cutaneous lesions. Our experience suggests that withdrawal of the drug and high dose corticosteroids is an effective treatment strategy. Disclosure of interest: None Declared.